Lutero y la astrología Cristo Redentor como referente de humildad y liberación de la conciencia pecadora - Baader, Bettine (Teología y vida, 2018)
The present research focus its attention on Martin Luther's theological thought in relation to Astrology. Based on some passages of the De Servo Arbitrio, we offer an analysis about Luther's Preface (1527) on German astrologer Johannes Lichtenberger's Prognosticatio in latino (1488). Those central arguments which derive from his doctrine of justification through faith will lead us to his opinion about his contemporaries astrological thought. On this occasion we want to demonstrate how the pessimism that characterises Lutheran doctrine on human free will, could be replaced by a conscious appreciation on Luther interest on Christian anxiety.